New training technologies and their use in training and development activities: Survey evidence from Lithuania - Kumpikaitė, Vilmantė; Čiarnienė, Ramunė (Journal of Business Economics and Management, 2008)
There is emerging evidence that new technologies are related to improvements in productivity. Nevertheless, in considering the relationship between new technology and productivity, it is vital to consider human resource management and development issues due to their mediating effects on the relationship between new technology and productivity. This paper focuses on training technologies, especially e‐learning. The increasing use of new technologies to deliver training and to store and communicate knowledge means that trainers must be technologically literate. That is, they must understand the strengths and weaknesses of new technologies and implementation issues such as overcoming users’ resistance to change. The paper reports the findings of a study of 724 Lithuanian employees, which revealed relatively weak usage of new technologies and e‐learning in human resource development processes. First published online: 14 Oct 2010